The Influence of motivation, training, and feedback on employee performance among support group of ministry of works in Kuala Lumpur - Norazah, Jaapar (2019)
This study aims to identify the influence of motivation, training and feedback on employee performance among members of the Executive Group in the Ministry of Works, Kuala Lumpur, Malaysia. This study used quantitative research methods by using questionnaires to collect the data. The sample using probability sampling method collected from a total of 217 members of the Support Group of grades 1-36. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 25.0. Different statistical research instrument used to test the reliability, descriptive analysis of the variables, correlation and regression analysis. The findings show the variable of feedback has the most dominant influence on employee performance (β = 0.364; t-value = 4.456), while the variables of motivation was the lowest effect on employee performance (β = 0.195; t-value = 2.854). However, all the variables have a positive correlation to employee performance.